2013
DOI: 10.1111/1469-0691.12255
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of gastrointestinal pathogens with a multiplex Luminex-based molecular assay in stool samples from diarrhoeic patients

Abstract: We have evaluated the multiplex molecular method xTAG(®) Gastrointestinal Panel (GPP) for detecting pathogens in stool samples of diarrhoeic patients. We collected 440 samples from 329 patients (male:female ratio of 1.2:1), including 102 immunosuppressed adults, 50 immunosuppressed children, 56 children attending the neonatal unit and 121 children attending the emergency unit. Of these, 176 samples from 162 patients were xTAG(®) GPP positive (102 viruses, 61 bacteria and 13 parasites) and the assay was more se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 27 publications
6
90
1
Order By: Relevance
“…Ten studies [20][21][22][23][24][25][26][27]29,30 reported results of association between the comparator and the GPP test in sufficient detail by pathogen to allow the construction of 2 × 2 tables by pathogen. These studies are further characterised in Table 7 and contributed data to the meta-analysis in Pathogen-level positive and negative agreement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies [20][21][22][23][24][25][26][27]29,30 reported results of association between the comparator and the GPP test in sufficient detail by pathogen to allow the construction of 2 × 2 tables by pathogen. These studies are further characterised in Table 7 and contributed data to the meta-analysis in Pathogen-level positive and negative agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study 11 differentiated between hospital-based samples (from children admitted with suspected viral gastroenteritis and children presenting to the emergency room) and community-based samples [adult and child travellers whose samples were submitted by general practitioners (GPs)]; the study population consisted of children and travellers only. Seven studies 19,22,26,27,29,35,39 reported the setting sufficiently to allow judgement on the origin of the infection (hospital vs. community). The majority of studies 11,12,20,21,[23][24][25]28,[30][31][32][33][34][36][37][38] reported recruitment of hospitalised patients, for which a mixed population should be assumed (in terms of origin of infection) as it is unclear at what point in time during hospitalisation each infection occurred.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations